Physical properties of sand parts produced using a Voxeljet VX1000 three-dimensional printer - Nyembwe, K.; Mashila, M.; Gonya, E.; Van Tonder, P.J.M.; De Beer, D.J. (South African Journal of Industrial Engineering, 2016)
Successful case studies of metal casting applications using sand moulds and cores produced by additive manufacturing (AM) processes have been widely reported in the literature. The layered-based manufacturing process has revolutionised traditional sand moulding methods. This is essentially due to the numerous advantages of AM, including the reduction of design lead time and the ability to manufacture objects with complex geometry in a rapid turnaround time. Locally-available AM processes that are capable of producing sand moulds and cores include laser sintering (LS) and three-dimensional printing (3DP), with the latter AM process growing in dominance over the former. However, a better understanding of the properties of parts produced by AM processes is required in order for the processes to be fully adopted by the foundry industry. Crucial characteristics of 3DP sand parts related to strength, dimensional accuracy, and hardness are not well-known in terms of their magnitude and in comparison with conventionally-moulded sand parts. In this investigation, the physical properties of test specimens produced under standard manufacturing conditions, using a Voxeljet VX1000 machine, were assessed for bend and tensile strength, hardness, friability, and surface finish. The physical properties of the 3DP test specimens were then compared with the properties of laboratory hand-rammed test specimens. The results of the investigation suggest that the properties of AM-fabricated sand parts are inferior to sand parts produced by conventional moulding processes. Gevallestudies van metaalgiettoepassings, wat van sand gietvorms en kerns gebruik maak wat met toevoegingsvervaardiging vervaardig word, is al volop gepubliseer. Die laag-gebaseerde vervaardigingsproses het die tradisionele sandgietvorm metodes totaal hervorm. Dit is hoofsaaklik as gevolg van die talryke voordele van toevoegings-vervaardiging. Dit sluit in die verkorting van die ontwerpleityd en die vermoë om ingewikkelde geometrieë in 'n vinnige omkeertyd te vervaardig. 'n Beter verstaan van die eienskappe van die onderdele, wat met toevoegings-vervaardigingtegnieke produseer word, is egter nodig voordat dit deur die gietbedryf aanvaar gaan word. Kritiese eienskappe van driedimensioneelgedrukte onderdele wat nie alombekend is nie is onder andere die sterkte, dimensionele akkuraatheid en hardheid. Die fisiese eienskappe van toetsmonsters is ondersoek vir buig- en treksterkte, hardheid, buigbaarheid, brosheid en oppervlak-afwerking. Die fisiese eienskappe van die toetsmonsters is vergelyk met die eienskappe van laboratorium, handgekompakteerde monsters. Die resultate toon dat die toevoegingsvervaardiging monsters se eienskappe slegter as die van konvensioneel gegiete monsters is.